if someone could please explain to me if im doing this wrong or what morei have to do to make it right
Follow Math Help Forum on Facebook and Google+
$\displaystyle -3 - \sqrt{1} = -3 - 1 = -4$
Originally Posted by skeeter $\displaystyle -3 - \sqrt{1} = -3 - 1 = -4$ the answer in the back says 3 - root 1 = 2
Originally Posted by realistic the answer in the back says 3 - root 1 = 2 sorry ... I just noted your last step. $\displaystyle -b - \sqrt{b^2-4ac}$ $\displaystyle -(-3) - \sqrt{1} = 3 - 1 = 2$
Originally Posted by skeeter sorry ... I just noted your last step. $\displaystyle -b - \sqrt{b^2-4ac}$ $\displaystyle -(-3) - \sqrt{1} = 3 - 1 = 2$ ah i see what i did wrong forgot that extra negative thanks for clearing that up for me
life is like that . . . . simple mistake that stucks us up.
View Tag Cloud